Public resistance in Russia: Mobilizational opportunities and the effect of protest on public attitudes - Gorbacheva, Elena; Slabinski, Daniella (2023)
The 2018–2020 “garbage” protests in Russia’s northerly Arkhangelsk Oblast’ have shown how an “apolitical” population can mobilize despite an increasingly repressive environment. Additionally, the Shiyes case may indicate the fate now facing Russian civic activism: mobilizational resources and experience have been weakened because many of the most experienced activists have had to leave Russia, while those who risked staying behind find themselves increasingly cut off from their colleagues in exile. Based on our analysis of the Shiyes case, as well as Russian civic activism more broadly, we argue that: • Russian civic activists have shown that it is possible to utilize mobilizational opportunities spurred by regime efforts to politicize “apolitical” issues. Protest participation in the “apolitical” Shiyes movement had an impact on political behavior, as evidenced by an increase in opposition votes. • Activists now in exile as well as those who have stayed behind are valuable carriers of mobilizational experiences. However, without continued Western support, mobilizational experiences and critical attitudes towards the Putin regime will remain an untapped resource. • Exchange of information and skills is needed in Russia; and in the West, reliable information from within Russia is sorely needed. Western donors and governments should therefore help to reduce the barriers that hamper the flow of information, e.g., by funding VPN (Virtual Private Network) services. Non peer reviewed